Billhub-consolidated bills management system - Cheah, Wei Heng (2024)
With the growth of the internet and technology, consumers are increasingly using subscription services. Many billing companies are promoting paperless and electronic billing to protect the environment. Consequently, online bill payments have become a necessity for bill payers. To encourage e-billing, each company has developed its own application for managing and paying bills. However, as the number of subscriptions rises, users have to use more and more applications to handle their growing number of bills, making the process tedious and repetitive. This increase in bills and the shift to paperless statements also leads to other issues such as missed payments, tracking errors, and financial management problems. To solve these problems, a consolidated billing system, BillHub was developed to help users manage and pay all their bills under a single application. The system includes features such as bill registration, the ability to pay multiple bills in one transaction, bill history, bill analysis, reminders, and auto-billing. The project was implemented using the React Native framework, with a Node.js server connecting to MongoDB. The server facilitates communication between bill payers and billing companies. The development followed an incremental model, focusing on one module at a time, starting with the most crucial features. After development, API testing ensured smooth communication between users, billing companies and server. Usability and user acceptance testing were conducted, with BillHub achieving a SUS score of 92.2, indicating high ease of use. Although the application includes multiple functionalities, it has not yet established business connections with any billing companies. Further promotion and collaboration with billing companies are needed for market deployment. Overall, the project is considered a success as it meets its objectives and scope.